EXPRESSION OF DMPN IN PSEUDOMONAS PUTIDA FOR DEGRADATION OF PHENOL IN SOIL - & Hetite, Dhari (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Background: Pseudomonas putida can efficiently degrade phenol. The aim of this study was to determine the level of expression of the decomposition of the biological bacteria pseudo-foul pseudomonas putida affected by pesticides. Methods: the study included the collection of 125 different soil samples from the soil surrounding the roots of different plants. Culturing and biochemical tests, also diagnostic devices using the Vitek system for diagnosis of Pseudomonas putida. genetic variation of genes responsible for biodegradation, polymerase chain reaction (PCR) was used to detect DmpN gene for molecular diagnosis and RT-PCR for gene expression. the results of the PCR showed that DmpN gene (199bp) exists in all P. putida.In conclusion: the study showed the importance of Pseudomonas putida for biological decomposition of phenol from the soil surrounding the roots of the plants.